Big data analytics for climate-smart agriculture in South Asia (Big Data 2 CSA): Developing data-driven and evidence-based solutions for problems constraining climate-smart agriculture in South Asia - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
Heterogeneity in soils, hydrology, climate, and rapid changes in rural economies including volatile prices, aging and shrinking farm workforces, agricultural feminization, and uneven market access are among the many factors that constrain the transition of South Asia’s cereal-based farming systems to climate-smart agriculture (CSA). Alternative approaches utilizing large heterogeneous datasets, however, remain insufficiently explored, though they can represent a powerful source of technology and management performance information. The big data analytics for climate-smart agriculture in South Asia (Big Data 2 CSA) project responds to thelimitations of plot-based agronomy by developing digital data collection systems to source, data-mine and interpret a wide variety of primary agronomic management and socioeconomic data from tens of thousands of smallholder rice and wheat farmers in India, Nepal and Bangladesh. This is carried out in partnership with national research systems and international partners in digital agriculture across the region.